Influence of periodontal disease, Porphyromonas gingivalis and cigarette smoking on systemic anti‐citrullinated peptide antibody titres. (1st August 2013) - Lappin, David F.; Apatzidou, Danae; Quirke, Anne‐Marie; Oliver‐Bell, Jessica; Butcher, John P.; Kinane, Denis F.; Riggio, Marcello P.; Venables, Patrick; McInnes, Iain B.; Culshaw, Shauna
Abstract: Background: Anti‐citrullinated protein antibody (ACPA) responses may precede clinical onset of rheumatoid arthritis. Porphyromonas gingivalis peptidylarginine deiminase can citrullinate proteins possibly inducing autoimmunity in susceptible individuals. Aim: To determine whether periodontitis, carriage of P. gingivalis, smoking and periodontal therapy influence ACPA titres. Methods: Serum and plaque samples were collected from 39 periodontitis patients before and after non‐surgical periodontal treatment, and from 36 healthy subjects. Carriage of P. gingivalis was determined by PCR of plaque DNA. ACPA was determined by anti‐cyclic citrullinated peptide (CCP) enzyme‐linked immunosorbent assay (ELISA). Anti‐ P. gingivalis titres were determined by ELISA. Results: Untreated periodontitis patients had higher anti‐CCP antibody titres than healthy controls [three patients (8%) greater than manufacturer suggested assay diagnostic threshold (5 Assay Units/AU) versus none (0%); mean ± SEM: 1.37 ± 0.23 versus 0.40 ± 0.10 AU, p < 0.0001]. Periodontitis patients who smoked demonstrated lower anti‐ P. gingivalis (15956 ± 4385 versus 2512 ± 1290 Units/ml, p < 0.05), but similar anti‐CCP than non‐smoking periodontitis patients (smokers: 1.31 ± 0.35; non‐smokers: 1.41 ± 0.32 AU). Healthy smokers demonstrated elevated anti‐CCP titres (0.75 ± 0.19 AU), at levels between healthy non‐smokers (0.15 ± 0.05 AU) and non‐smoker periodontitis patients. Six months after periodontal treatment, there were significant reductions in anti‐CCP (non‐smokers p < 0.05) and anti‐ P. gingivalis (all participants p < 0.01). Conclusion: In subjects with periodontitis, P. gingivalis infection may be responsible for inducing autoimmune responses that characterize rheumatoid arthritis.